Formulation and Physical Properties of Anti Foot Odor Spray from Lemon (Citrus limon Burm. F.) - Nurul Hidayati; Maulida Kurniasari; Avanilla Fany Septyasari (Urecol Journal. Part G: Multidisciplinary Research, 2021)
Lemon (Citrus limon Burm. F.) contains essential oil in the form of limonene which has antibacterial activity against Staphylococcus epidermidis which causes foot odor. To facilitate the application, it is made in the form of a spray, because the spray has a fast-drying profile so it is easy to use. This study aims to determine the effect of variations in the concentration of lemon essential oil on the physical properties of foot odor spray and to determine the concentration of lemon essential oil which produces an anti-foot odor spray with good physical properties. Spray made with variations in the concentration of essential oils 5%, 10%, and 15%. The spray was then tested for its physical properties including organoleptic, homogeneity, pH, and viscosity tests. The results of the organoleptic test and the homogeneity test were analyzed descriptively, while the results of the pH test and viscosity test were analyzed by one-way ANOVA with a 95% confidence level. The results showed that the increase in the concentration of lemon essential oil affected the organoleptics and increased the viscosity value. The 5% concentration spray produced the best physical properties with a liquid form, cloudy white color, distinctive lemon aroma, homogeneous with a pH value of 6 Â± 0, and a viscosity value of 0.53 Â± 0.06 dPas.